Interferon alpha and beta receptor 1 knockout in human embryonic kidney 293 cells enhances the production efficiency of proteins or adenoviral vectors related to type I interferons - Kim, Aro; Park, Jong-Hyeon; Lee, Min Ja; Kim, Su-Mi (Frontiers in Bioengineering and Biotechnology, 2023)
Human embryonic kidney (HEK) 293 cells are widely used in protein and viral vector production owing to their high transfection efficiency, rapid growth, and suspension growth capability. Given their antiviral, anticancer, and immune-enhancing effects, type I interferon (IFN)s have been used to prevent and treat human and animal diseases. However, the binding of type I IFNs to the IFN-α and -β receptor (IFNAR) stimulates the expression of IFN-stimulated genes (ISGs). This phenomenon induces an antiviral state and promotes apoptosis in cells, thereby impeding protein or viral vector production. In this study, we generated an IFNAR subtype 1 knockout (KO) HEK 293 suspension (IFNAR-KO) cell line by using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein-9 nuclease (Cas9) technology. Upon treatment with human IFN-α, the IFNAR-KO cells showed a constant expression of ISGs, including 2ʹ-5ʹ-oligoadenylate synthetase 1 (OAS1), myxovirus resistance 1 (Mx1), protein kinase RNA-activated (PKR), and IFN-induced transmembrane protein 1 (IFITM1), when compared with the wild-type HEK 293 (WT) cells, where the ISGs were significantly upregulated. As a result, the titer of recombinant adenovirus expressing porcine IFN-α was significantly higher in the IFNAR-KO cells than in the WT cells. Furthermore, the IFNAR-KO cells continuously produced higher amounts of IFN-α protein than the WT cells. Thus, the CRISPR-Cas9-mediated IFNAR1 KO cell line can improve the production efficiency of proteins or viral vectors related to IFNs. The novel cell line may be used for producing vaccines and elucidating the type I IFN signaling pathway in cells.